THE EXPRESSION OF MEANING IN THE LANGUAGE STYLE OF THE QUR’AN: A BAL?GHAH PERSPECTIVE - Kenny Andika; Asrina Asrina; Syofyan Hadi (Lingeduca: Journal of Language and Education Studies, 2026)
The expression of meaning in the Qur’an constitutes an essential aspect of bal?ghah studies, demonstrating the linguistic excellence of the revealed text. Meaning in the Qur’an is not merely literal; rather, it is constructed through the interaction between linguistic structure, context, and rhetorical devices. This study aims to comprehensively examine the expression of meaning in the language style of the Qur’an from the perspective of bal?ghah. This research employs a descriptive qualitative approach using the library research method, drawing upon various scholarly works related to ‘ilm al-ma‘?n?, ‘ilm al-bay?n, and ‘ilm al-bad?‘ as the primary data sources. The data were analyzed through content analysis focusing on the expression of meaning. The findings reveal that meaning in the Qur’an is contextual and dynamic, developed through the harmony between structure and context (‘ilm al-ma‘?n?), the variation of implicit and symbolic expressions (‘ilm al-bay?n), and the reinforcement of aesthetic and rhetorical elements (‘ilm al-bad?‘). These three aspects function integratively in producing meanings that are not only linguistically precise but also rhetorically persuasive and aesthetically powerful. This study underscores the importance of a holistic approach to understanding the language style of the Qur’an and contributes conceptually to the development of Qur’anic linguistic studies based on bal?ghah.